Survival after second and subsequent recurrences in osteosarcoma: a retrospective multicenter analysis. Issue 3 (June 2018) - Tirtei, Elisa; Asaftei, Sebastian D.; Manicone, Rosaria; Cesari, Marilena; Paioli, Anna; Rocca, Michele; Ferrari, Stefano; Fagioli, Franca
Purpose: Osteosarcoma (OS) is the most common primary bone tumor. Despite complete surgical removal and intensive chemotherapeutic treatment, 30%-35% of patients with OS have local or systemic recurrence. Some patients survive multiple recurrences, but overall survival after OS recurrence is poor. This analysis aims to describe and identify factors influencing post-relapse survival (PRS) after a second OS relapse. Methods: This is a retrospective analysis of 60 patients with a second relapse of OS of the extremities in 2 Italian centers between 2003 and 2013. Results: Treatment for first and subsequent relapses was planned according to institutional guidelines. After complete surgical remission (CSR) following the first recurrence, patients experienced a second OS relapse with a median disease-free interval (DFI) of 6 months. Lung disease was prevalent: 44 patients (76%) had pulmonary metastases. Survival after the second relapse was 22% at 5 years. Lung disease only correlated with better survival at 5 years (33.6%) compared with other sites of recurrence (5%; p = 0.008). Patients with a single pulmonary lesion had a better 5-year second PRS (42%; p = 0.02). Patients who achieved a second CSR had a 5-year second PRS of 33.4%. Chemotherapy (p<0.001) benefited patients without a third CSR. Conclusions: This analysis confirms the importance of an aggressive, repeated surgical approach. Lung metastases only, the number of lesions, DFI and CSR influenced survival. It also confirms the importance of chemotherapy in patients in whom surgical treatment is not feasible.